1972
DOI: 10.1055/s-0038-1649349
|View full text |Cite
|
Sign up to set email alerts
|

The Kinin System of Human Plasma

Abstract: SummaryHuman plasma was adsorbed to celite. The celite eluates were chromatographed on QAE-Sephadex A-50, followed by gel filtration, isoelectric focusing and preparative polyacrylamide electrophoresis.By anion-exchange chromatography, factor XI a, kallikrein and y-globulin were isolated from the excluded protein peak. Factor XIa (MW ∼170,000) corrected the deficiency in plasmas deficient in factors XII or XI, but had no effect on the kininsystem. Its isoelectric point was about 8.0-8.5. Kallikrein had a molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…It seems that, following exposure t o immune precipitates, but particularly celite, most of factor XIIa appears as an anionic fragmen t , which, although acquiring pre kallikrein-ac t iva ting activity, still retains some clot-promoting activity, which corrects the clotting defect in factor Xll-deficient plasma, but not that of plasmas deficient in other clotting factors. The clot-promoting activity and PKA-activity is similar to material obtained under similar conditions from human plasma, where we have proposed t o designate the fragment derived from XlIa as "Xllf" [25]. The acquisition of PKA-activity is paralleled by a loss of clot-promoting activity, as will be described in a succeeding paper and represents circumstantial evidence that factor XIIa is converted t o XIIf or PKA.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It seems that, following exposure t o immune precipitates, but particularly celite, most of factor XIIa appears as an anionic fragmen t , which, although acquiring pre kallikrein-ac t iva ting activity, still retains some clot-promoting activity, which corrects the clotting defect in factor Xll-deficient plasma, but not that of plasmas deficient in other clotting factors. The clot-promoting activity and PKA-activity is similar to material obtained under similar conditions from human plasma, where we have proposed t o designate the fragment derived from XlIa as "Xllf" [25]. The acquisition of PKA-activity is paralleled by a loss of clot-promoting activity, as will be described in a succeeding paper and represents circumstantial evidence that factor XIIa is converted t o XIIf or PKA.…”
Section: Discussionsupporting
confidence: 54%
“…also been found in celite eluates (with similar properties) of human plasma [25], it is believed t o represent a fragment of plasma kallikrein.…”
mentioning
confidence: 79%
“…Regulation of this system, as is the case with the other pathways, has been primarily examined by interacting the highly purified components of the system with isolated plasma inhibitors. A critical control protein operative at the common initiating step for all three Hageman factor dependent pathways is the inhibitor of the activated first component of complement, Cl inhibitor (Cī INH), which has now been isolated from human plasma in highly purified form by several methods [18,38,47]. It appears to be a heat and acid labile alpha-2 globulin which reacts rapidly and stoichiometrically with the activated first component of complement CL Studies by Pensky and Schwick [40] suggest immunochemical similarity if not identity with an alpha-2 neuraminoglycoprotein of human plasma.…”
Section: The Fibrinolytic Systemmentioning
confidence: 99%
“…Forbes, Pensky and Ratnoff originally demonstrated the capacity of Cī INH to inhibit the action of activated Hageman factor in clotting assays [6]. Studies have also revealed that partially purified Cī INH suppresses the esterase activity of the 37,000 molecular weight Hageman factor fragment on benzoyl arginine ethyl ester [38] and is effective in inhibiting activated Hageman factor or the Hageman factor fragments' capacity to generate plasminogen activator from plasminogen proactivator in a system utilizing purified components [47]. Inhibition by Cī INH was achieved in a dose dependent fashion.…”
Section: The Fibrinolytic Systemmentioning
confidence: 99%
See 1 more Smart Citation